2012
DOI: 10.4028/www.scientific.net/msf.723.445
|View full text |Cite
|
Sign up to set email alerts
|

Development and Key Technologies of High-Speed Grinding

Abstract: The mechanism and characteristic of high speed grinding and the technology and development of high speed grinding were introduced. High efficiency grinding including ultrahigh speed grinding, high efficiency deep grinding, creep deep grinding and abrasive belt grinding was analyzed. The technology about manufacturing the spindle system in super high speed grinding and the other main interrelated technology about grinding were also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…There are a large number of machines used for grinding solid and lumpy materials. The choice of a mill for industrial and research purposes should be carried out taking into account the specific properties of the material to be grind and the conditions of its use [4]- [7]. Materials of metallurgical and foundry refractories (bricks of various configurations) are ground in ball mills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a large number of machines used for grinding solid and lumpy materials. The choice of a mill for industrial and research purposes should be carried out taking into account the specific properties of the material to be grind and the conditions of its use [4]- [7]. Materials of metallurgical and foundry refractories (bricks of various configurations) are ground in ball mills.…”
Section: Introductionmentioning
confidence: 99%
“…These bricks are lining materials for blast furnaces, converter furnaces, electric arc furnaces and bottom refractories for induction and thermal heating furnaces. We found that all mills operating with grinding media are the most common type of grinders [5], contaminate the final product and overheating [7], [8]. It has been established that in the waterfall mode of a ball mill, the balls falling on the balls cut out thin steel petals from them so that about 150-200 grams are collected in one ton of grinding of such chips.…”
Section: Introductionmentioning
confidence: 99%